Speech-in-noise discriminability after noise exposure: Insights from a gerbil model of acoustic trauma - Carolin Jüchter; Rainer Beutelmann; Sonny Bovee; Katja Bleckmann; Georg Martin Klump (PLoS ONE, 2025)
Speech comprehension, especially in the presence of background sounds, allegedly declines as a consequence of noise-induced hearing loss. However, the connection between noise overexposure and deteriorated speech-in-noise perception despite normal audiometric thresholds (hidden hearing loss) is not yet clear. This study investigates speech-in-noise discrimination in young-adult Mongolian gerbils before and after an acoustic trauma to examine the link between noise exposure and speech-in-noise perception. Nine young-adult gerbils were trained to discriminate a deviant consonant-vowel-consonant combination (CVC) or vowel-consonant-vowel combination (VCV) in a sequence of CVC or VCV standards, respectively. The logatomes were spoken by different speakers and masked by a steady-state speech-shaped noise. After the gerbils obtained the behavioral baseline data, they underwent an acoustic trauma and participated in the behavioral experiments again. Applying multidimensional scaling, response latencies were used to generate perceptual maps reflecting the gerbils’ internal representations of the sounds pre- and post-trauma. To evaluate how the discrimination of vowels and consonants was altered after noise exposure, changes in response latencies between phoneme pairs were investigated in relation to their articulatory features. Numbers of intact inner hair cell synapses were counted, and auditory brainstem responses were measured to assess peripheral auditory function. Perceptual maps of vowels and consonants were very similar before and after noise exposure. Interestingly, the gerbils’ overall vowel discrimination ability was improved after the acoustic trauma, even though the gerbils suffered from noise-induced hearing loss with a temporary threshold shift for frequencies above 4 kHz. In contrast, there were only minor changes in the gerbils’ consonant discrimination ability. Moreover, noise exposure showed a differential influence on response latencies for vowel and consonant discriminations depending on the articulatory features. Altogether, the results show that an acoustic trauma followed by a temporary threshold shift is not necessarily linked to speech-in-noise perception difficulties associated with hidden hearing loss.